2016
DOI: 10.1097/sla.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospital Characteristics on Failure to Rescue Following Major Surgery

Abstract: Objective To determine the effect of hospital characteristics on failure to rescue after high-risk surgery in Medicare Beneficiaries. Summary Background Data Reducing failure to rescue events is a common quality target for U.S. hospitals. Little is known about which hospital characteristics influence this phenomenon and more importantly by how much. Methods We identified 1,945,802 Medicare beneficiaries undergoing one of six high-risk general or vascular operations between 2007-10. Using multilevel mixed-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(83 citation statements)
references
References 33 publications
0
81
1
1
Order By: Relevance
“…Data from the American College of Surgeons National Surgical Quality Improvement Program 28 and Medicare 29 on postoperative mortality rates have shown that failure to rescue, rather than overall mortality, is strongly dependent on hospital volume. A subsequent analysis 30 found that it was mainly hospital status (academic versus non-academic), ICU capacity and academic character that determined the failure-to-rescue rate. A study 31 focusing on failure to rescue after colorectal resection in the Netherlands demonstrated that low-level ICU care in particular was associated with increased failure-to-rescue rates.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the American College of Surgeons National Surgical Quality Improvement Program 28 and Medicare 29 on postoperative mortality rates have shown that failure to rescue, rather than overall mortality, is strongly dependent on hospital volume. A subsequent analysis 30 found that it was mainly hospital status (academic versus non-academic), ICU capacity and academic character that determined the failure-to-rescue rate. A study 31 focusing on failure to rescue after colorectal resection in the Netherlands demonstrated that low-level ICU care in particular was associated with increased failure-to-rescue rates.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies and the literature, the reasons for suboptimal outcomes in certain hospital settings are likely to be multifactorial and include differences in staffing levels and skills [27][28][29][30][31] ; in resources, services, infrastructure, technologies, and available equipment 23,[30][31][32] ; in experience driven by the patient volume 30,33 ; in compliance with treatment guidelines 34 ; and in postoperative complication management. 23,32 In contrast to our findings of significant differences between urban teaching, nonteaching, and rural hospitals by insurance status, Bhattacharyya et al 31 analyzed data from the NIS and did not find any significant difference in the distribution of HNC patients by insurance status (payer mix) in teaching hospitals versus nonteaching hospitals in 2010. These differences might be the result of the different categorization of a hospital's teaching status in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested strategies are demanding: understanding of the single hospital system, caregivers, available resources; implementing process methods to effectively learn from failure to rescue events; improving hospital safety culture (30,44).…”
Section: Introductionmentioning
confidence: 99%